Theoretical-practical reflections around the applying of legal rule in time within Administrative law - Jiménez Alemán, José Alonzo (2020)
This article aims to make a theoretical-practical contribution to the development of any institution linked to the applicability of regulations over time. To meet his object the author raises legal cases based on his own professional experience. It is intended that this paper could be read with an administrative law point of view, so the development of this article could be used as a parameter of legality in the face of gaps in the special regulations.